PENGARUH JUMLAH KANTOR, INFLASI, NILAI TUKAR, SUKU BUNGA DAN PDB TERHADAP DPK PADA BANK UMUM SYARIAH DI INDONESIA PERIODE 2017-2022 - Putri Herma Syasya; Fitria Rahmah; Nurul Fadhilah (FEBI Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
It is important to know the factors that influence Third Party Funds (DPK), because Third Party Funds (DPK) support stability and management in sharia commercial banks. This research aims to determine the influence of the number of offices, inflation, exchange rates, interest rates, and Gross Domestic Product (GDP) on Third Party Funds (DPK) in Islamic commercial banks in Indonesia for the 2017-2022 period.The research method used is a quantitative approach. The population of all BUS in Indonesia for the 2017-2022 period and the sample used was a saturated sampling method. The data used is secondary data with a documentation method, namely data collection through official websites such as the Financial Services Authority (OJK), Bank Indonesia (BI), and the Central Statistics Agency (BPS). The data analysis technique uses multiple linear regression analysis with the Eviews 10 application.The research showed that partially the number of offices, exchange rates, interest rates, and Gross Domestic Product (GDP) had a significant effect on Third Party Funds (DPK) in Islamic commercial banks in Indonesia for the 2017-2022 period, while inflation had no significant effect on Third Party Funds (DPK) in Islamic commercial banks in Indonesia for the 2017-2022 period. Then simultaneously the number of offices, inflation, exchange rates, interest rates, and Gross Domestic Product (GDP) have a significant effect on Third Party Funds (DPK) in Islamic commercial banks in Indonesia for the 2017-2022 period. For future researchers, to add internal variables from other Islamic commercial banks to get more accurate results.